Marketing Communication Strategies For Asap Tilapia (Oreochromis niloticus) Products In Tebing Tingg Village, Benai District, Kuantan Singingi Regency, Riau Province - Febrian Febrian; Zulkarnain Umar; Kusai Kusai (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
The purpose of this study is to analyze the Strengths, Weaknesses, Opportunities, and Threats in marketing smoked tilapia products in Tebing Tinggi Village, and analyze marketing communication strategies for smoked tilapia processing in Tebing Tinggi Village. This research was conducted in February 2021 at Tebing Tinggi Village, Benai District, Kuantan Singingi Regency, Riau Province. This research was conducted with a qualitative approach because the problems related to humans are fundamentally dependent on observation. The data collected consists of primary and secondary data. Data collection was carried out in this study by interview, observation, and documentation, and for the determination of informants by Snowball Sampling with a total of 9 informants which included 2 village officials, 2 consumers, and 5 smoked tilapia fish processors. Asap Tilapia (Oreochromis niloticus) processors in Tebing Tinggi Village use the most effective form of communication, using Interpersonal Communication. Furthermore, the marketing communication mix used in Tebing Tinggi Village is Direct Marketing, Promotion, Personal Selling, Advertising and Public Relations.